The usability of virtual reality to train individuals in responding to behaviors related to dementia - Garcia, Linda; Robitaille, Annie; Bouchard, Stéphane; Rivard, Marie-Christine; McCleary, Lynn (Frontiers in Dementia, 2024)
Dementia is associated with several behavioral changes globally referred to as Behavioral and Psychological Symptoms of Dementia (BPSD) of which many are recognized to be the expression of unmet needs triggered by environmental factors. BPSD are an extreme source of stress for family care partners and health care providers alike and can be the reason why people living with dementia (PLWD) are placed in long-term care homes (LTCH). The overall goal of this project was to examine whether a virtual environment that includes a virtual LTCH resident with dementia in a lifelike situation could be useful and usable for health care providers and care partners to identify potential triggers to BPSDs while being engaged emotionally with the scenario. Twenty-three health care professionals working with PLWD, 25 care partners to PLWD, 27 students in a health-related field, and 11 university/community college faculty members teaching courses relevant to gerontology tested the application which depicted a meal-time scenario. In addition to being asked about the behavioral triggers in the scene, participants were asked about the usefulness and usability of the tool for training. Presence and simulator sickness were also measured. Results suggest that participants generally felt present and emotionally engaged. They could identify the potential triggers for the observed behaviors in the virtual human with dementia as well as suggest some solutions. The majority (87% of participants) found the tool easy to use. Many participants identified the inability to interact with the virtual humans as a shortfall, and few reported mild to moderate levels of simulator sickness. As the behavioral changes associated with dementia can cause extreme stress for those interacting with PLWD, developing an effective and efficient training tool could significantly improve well-being for all involved. The investigators see the development and testing of an interactive version of this virtual environment as a next step in making this a clinically relevant training tool.